Menjemput Arsip Hingga ke Belanda: Dari Praktik Manajemen Arsip hingga Akereditasi Kearsipan PT Semen Padang - Putra, Purwanto (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
This study was conducted with the aim of highlighting the importance of archive management and practices at PT Semen Padang. That the extent to which information, records and archives are the "blood" for the continuation of any organization or institution that is used as the basis for making every decision. Poor records management not only hinders the organizational development process but also leads to ineffectiveness and inefficiency in service delivery. Various types of archives, both personal and especially those that are official belonging to organizations or institutions, in this case especially PT Semen Padang, are very important to be traced, collected and preserved wherever they are in order to support the life of the PT Semen Padang organization. This research uses a qualitative approach, with data collection methods based on document studies, archives and observations. The documents and archives consist of published and unpublished sources, including institutional reports, actions and various conference materials, which the researcher uses for reference and writing materials. This type of research is descriptive-narrative research. The research results of PT Semen Padang, which has obtained archival accreditation A once again shows its commitment to archival affairs. The company as optimally as possible continuously strives to create an archival culture according to the dynamics of advancing society, nation and state in accordance with future needs. The success of PT Semen Padang in obtaining A accreditation also cannot be separated from archive management practices that are carried out effectively, the required records are available at the right time to support business activities.